2015
DOI: 10.1097/aog.0000000000000602
|View full text |Cite
|
Sign up to set email alerts
|

Use of Granulocyte Colony-Stimulating Factor During Pregnancy in Women With Chronic Neutropenia

Abstract: Objective To report outcomes associated with the administration of granulocyte colony–stimulating factor (G-CSF) to women with chronic neutropenia during pregnancy. Methods We conducted an observational study of women of child-bearing potential with congenital, cyclic, idiopathic, or autoimmune neutropenia enrolled in the Severe Chronic Neutropenia International Registry to determine outcomes of pregnancies, without and with chronic G-CSF therapy, 1999–2014. Treatment decisions were made by the patients’ per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 20 publications
0
42
0
3
Order By: Relevance
“…It must be realized that NAIN, causing fulminant infections, can be a potentially fatal condition. Several case reports about severe sepsis or meningitis as a result of NAIN have been published [15,48,49,50]. As was described in the report of Lalezari et al [3], infections are not always immediately present, but often start several days after birth.…”
Section: Symptomsmentioning
confidence: 76%
“…It must be realized that NAIN, causing fulminant infections, can be a potentially fatal condition. Several case reports about severe sepsis or meningitis as a result of NAIN have been published [15,48,49,50]. As was described in the report of Lalezari et al [3], infections are not always immediately present, but often start several days after birth.…”
Section: Symptomsmentioning
confidence: 76%
“…In one study of 107 women reporting on 224 pregnancies treatment with G-CSF (median dose 1.0 mcg/kg per day) in spontaneous terminations or preterm labors, and a suggestion of benefit. [35] Adverse events in the neonates were similar for the two groups. Another study analyzing 38 pregnancies, 21 in women with CIN, also showed no differences in outcomes with or without treatment for the mothers or their newborns.…”
Section: Pregnancymentioning
confidence: 88%
“…[36] Transient profound neutropenia in infants born to women with CIN or AIN sometimes with severe infectious ramifications were also reported. [35, 36] Clinically this means that blood counts should be done at least a few times after birth in infants of mothers with CIN or AIN. If the neonate is severely neutropenic and there is concern about the risk of severe infections, G-CSF may be helpful in this specific setting.…”
Section: Pregnancymentioning
confidence: 99%
“…Clinical experience is currently restricted to postchemo/postauto-transplant neutropenia and autologous/allogeneic stem cell mobilization. Thus far, no data were reported on granulocyte mobilization for preparative apheresis [40] or on congenital and acquired neutropenias [41,42]. While several studies report financial benefits for the healthcare system, these focus on G-CSF costs and prescribing behavior.…”
Section: What Is the Expected Benefit Of Biosimilars?mentioning
confidence: 98%